Are SME’s Product and Local Government Programs (OVOP)Coherent? - Shohibul MA, Ana; Sarjiyanto, Sarjiyanto; Sarwoto, Sarwoto (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
In the developing countries, the government has a vital role in supporting the development of SME’s as one of economic pillars. There are studies which state that the government has played an active role in supporting the development of SME’s, either from policy or implementation, but several studies argue that government failure in supporting and creating business climate has caused business stagnation for SME’s. This study aims to analyze the coherence between government policy through Regional Superior Products development (under OVOP) program with SME’s main product choice in Central Java province. The analysis using analytic hierarchy process (AHP), on the data collected through focus group discussion (FGD), questionnaire, and secondary data. The result of this study shows weak evidence that there is coherence between government program and SME’s/ SME’s main product choice, there are only 6 districts/cities that have coherence SME’s: Grobogan district, Blora, Rembang, Magelang (city), Brebes, and Banjarnegara, while the rest districts/cities have no coherence between SME’s and government policy. Supply side policy, volume orientation, partial support, and several other factors are the cause of in-coherence. The implication of this finding is that there is a need of evaluation, downstream policy, business link (including education field) that support SME’s will develop.